Modified Anterolateral Approach for Total Ankle Arthroplasty. Issue 2 (21st June 2021) - Hirao, Makoto; Ebina, Kosuke; Etani, Yuki; Kaneshiro, Shoichi; Tsuboi, Hideki; Noguchi, Takaaki; Okamura, Gensuke; Kunugiza, Yasuo; Nakaya, Hiroyuki; Nishikawa, Masataka; Tsuji, Shigeyoshi; Takahi, Koichiro; et al.
: Level of Evidence: Level V.